Management of critically ill septic patients with diabetes - Choudhury, Arnab; Kumar, Sahil; Kumar, Nitin; Bairwa, Mukesh (International Journal of Research in Medical Sciences, 2022)
Diabetes and sepsis are major contributors of morbidity and mortality around the world, with diabetic patients accounting for the majority of post-sepsis comorbidities and escalating mortality rates. Diabetes is undoubtedly a key comorbid syndrome due to its high frequency and propensity to affect critical parts of sepsis pathogenesis; however, the precise impact of diabetes on infection and sepsis progression is elusive. In diabetic individuals with sepsis, dysfunctional immunological pathways, which are frequent in both sepsis and diabetes, promotes worsening of the host response. The effect of diabetes on sepsis mortality is still debatable. While poor glycemic management is linked to the incidence of a large proportion of severe infections, treatment with insulin or commercially available oral antidiabetic drugs are linked to lower sepsis incidence and even death. Optimal glycemic control has been reported to improve immunological adaptability, resulting in a lower mortality rate in diabetes patients with sepsis. The present review is an attempt to gather literature pertinent to glycemic control and risk of sepsis. An additional body of reports are also included on the effect of insulin and other anti-diabetic medications on the incidence and mortality for sepsis along with the strategies employed for the management of the said illness.